The Effect of Reward and Punishment Implementation on Improving Students' Disciplined Character Through Football Learning at Sape 9th State Elementary School in 2026 - Ilman Nafiyah; Mujriah Mujriah; Supriadin Supriadin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aimed to examine the effect of implementing reward and punishment strategies on improving students’ discipline character through football learning at SDN 9 Sape in 2026. The study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The participants consisted of 51 elementary school students. Data were collected using a discipline character observation sheet covering punctuality, compliance with rules, responsibility, and discipline during learning activities. Data analysis included descriptive statistics, the Kolmogorov–Smirnov normality test, the Paired Sample t-Test, and effectiveness analysis using N-Gain and Effect Size (Cohen’s d). The results revealed that the mean discipline character score increased from 67.67 in the pre-test to 84.76 in the post-test, representing an improvement of 17.09 points (25.25%). The Paired Sample t-Test indicated a significance value of 0.000 (p < 0.05), demonstrating a significant effect of the implementation of reward and punishment on students’ discipline character. Furthermore, the N-Gain value of 0.53 was categorized as moderate, while the Cohen’s d value of 4.38 indicated a very large effect size. These findings suggest that the implementation of reward and punishment in football learning is effective in improving students’ discipline character. This study contributes to the development of physical education learning strategies that support character education strengthening as well as the implementation of the Merdeka Curriculum and the Pancasila Student Profile in elementary schools.